Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Pada Perusahaan Sub Sektor Otomotif Dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Periode 2014 â€“ 2018 - Mardiana, Mardiana; Verahastuti, Camelia; Nur, Rosita (Media Ekonomi, 2021)
This study aims to determine and analyze the effect of Current Ratio (CR), Total Asset Turnover (TATO), and Return On Asset (ROA) on profit growth in automotive sub-sector companies and components listed on the Indonesia Stock Exchange for the period 2014-2018. used in this study is secondary data sourced from annual performance summary data of listed companies, obtained from thewebsite officialÂ www.idx.co.id.. The results of the study partially show that thevariable Current Ratio (CR)has a negative and insignificant effect on profit growth;variable Total Asset Turnover (TATO)has a negative and insignificant effect on profit growth; while the variable Return on Assets (ROA) has a significant positive effect on profit growth. Simultaneously, it shows that the variables Current Ratio (CR), Total Asset Turnover (TATO), and Return On Asset (ROA) have a significant effect on profit growth.